Convivialidade e performance na experiência estética dos jovens hip hoppers da Força Hip Hop em Fortaleza - Fragoso, Tiago de Oliveira (2011)
This study represents an investigation of the aesthetic and social experience for young break dancers graffiti artists and rappers in one of the organizations representing the hip hop movement in Fortaleza the Hip Hop Force whose headquarters are located in the community in the San Francisco suburbs of urban. We tried to understand the relationship between the expression of artistic elements with emphasis on break dancing and the formation of an intense aesthetic-social youth friendliness. From the perspective of the anthropology of performance / experience of Victor Turner of the analysis of contemporary sociability Mafesoli from studies on youth and hip hop it was to describe and / or understand the constitution of an aesthetics of everyday life lived in these young. Through the practice of artistic elements and expressive style of living the young Force Hip Hop seems to create an intense conviviality a way of being / living together dynamic confrontational playful ritualized performative which is presented in the most expressive collective practice of dance music and painting. For this work was made an ethnographic fieldwork with intense participation in the daily life of these subjects and were also conducted semi-structured with pre-defined on the aesthetic experience, stylistic of some of these young people.